2021
DOI: 10.24926/iip.v12i1.3353
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Students to Engage in Preparation for Flipped Classrooms by Using Embedded Quizzes in Pre-class Videos

Abstract: Background: The success of flipped classrooms is dependent upon students’ preparation prior to class, the lack of which is the most common challenge associated with this teaching methodology. To mitigate this limitation, it is important to develop and assess methods of engaging learners during pre-class activities. Objective: To determine if quiz delivery method (embedded throughout versus after pre-class videos) affects students’ knowledge retention, grades, and video viewing behavior. Methods:  Participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Another potential limitation of the resource could be the lack of an engaging activity or practice questions embedded within the video that can help the user assess their progress. One study aimed to investigate whether the incorporation of quizzes within pre-class videos that first year pharmacy students needed to watch prior to attending a lecture resulted in better memory retention, student performance, and amount of time spent on watching the pre-class videos [ 50 ]. The study showed that students who completed the quizzes that were embedded in the pre-class videos performed similarly for both the pre- and post-class quizzes to students that completed the quizzes after they watched the pre-class videos [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another potential limitation of the resource could be the lack of an engaging activity or practice questions embedded within the video that can help the user assess their progress. One study aimed to investigate whether the incorporation of quizzes within pre-class videos that first year pharmacy students needed to watch prior to attending a lecture resulted in better memory retention, student performance, and amount of time spent on watching the pre-class videos [ 50 ]. The study showed that students who completed the quizzes that were embedded in the pre-class videos performed similarly for both the pre- and post-class quizzes to students that completed the quizzes after they watched the pre-class videos [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study aimed to investigate whether the incorporation of quizzes within pre-class videos that first year pharmacy students needed to watch prior to attending a lecture resulted in better memory retention, student performance, and amount of time spent on watching the pre-class videos [ 50 ]. The study showed that students who completed the quizzes that were embedded in the pre-class videos performed similarly for both the pre- and post-class quizzes to students that completed the quizzes after they watched the pre-class videos [ 50 ]. Despite this, students who completed the quizzes that were embedded in the pre-class videos were more likely to view these videos in contrast to students that watch the pre-class videos that did not contain any quiz questions in them [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These quizzes are typically included within the video and allow students to pause and answer questions related to the content they just learned. The purpose of these quizzes is to help students stay engaged while watching lecture videos, as well as to reinforce the concepts covered in the video (Jones et al, 2021). They also provide immediate feedback to students, allowing them to identify areas where they may need further review or clarification and to test their understanding of concepts (Jones et al, 2021).…”
Section: Quizzes In Lecture Videosmentioning
confidence: 99%